The Perils of Multi-lingual Students: “I’m Not LD, I’m L2 or L3.” - Kim, Kioh; Helphenstine, Derrick T. (Journal of International Students, 2017)
As more companies and families expand to the global market an increasing number of students are entering international schools outside of their home countries. Each international school is governed and run according to their own policies, but one overarching element remains: the language of instruction is usually English. When English Language Learners enter English dominant environments they often have difficulties acclimating to the language and the classroom. In this paper the authors intend to address some myths about ELL students in the classroom, and shed light on why some students are wrongly identified as having possible SLDs and how we can better help students by looking further at their characteristics.